2020
DOI: 10.1093/jas/skaa009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of statistical process control procedures to identify deviations in continuously measured physiologic and behavioral variables in beef steers experimentally challenged with Mannheimia haemolytica

Abstract: The objective of this experiment was to determine if statistical process control (SPC) procedures coupled with the remote continuous collection of feeding behavior patterns, accelerometer-based behaviors, and rumen temperature can accurately differentiate between animals experimentally inoculated with Mannheimia haemolytica (MH) or PBS. Thirty-six crossbred steers (BW = 352 ± 23 kg) seronegative for MH were randomly assigned to bronchoselective endoscopic inoculation with MH (n = 18) or PBS (n = 18). Electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…AFS, such as automated milk dispensers for pre-weaned calves and automatic concentrate bunks for post-weaned calves, and water bins, have been used in studies aimed at automated health monitoring in young calves, hence stage two research. These AFS can measure a wide range of parameters linked to feeding and drinking patterns, including daily feed intake (4, 45, 47, 52-55, 57, 72-74), frequency and duration of rewarded and unrewarded visits (4, 45, 47, 52-55, 57, 58, 61, 62, 72, 74), drinking speed (milk) (47, 52-54), water-drinking behavior (intake, time, and frequency) (62,74), and other feeding behaviors (head-down duration at the AFS) (55, 72), time-to-bunk: time to approach feeding stations following feed-truck delivery (55, 72), and duration of unrewarded visit intervals (55). We did not find validation studies for common systems such as Förster-Technik GmbH (n = 5; Engen, Germany) or GrowSafe Systems (n = 3; GrowSafe Systems Ltd., Airdrie, AB, Canada).…”
Section: Automatic Feeding Stationsmentioning
confidence: 99%
See 1 more Smart Citation
“…AFS, such as automated milk dispensers for pre-weaned calves and automatic concentrate bunks for post-weaned calves, and water bins, have been used in studies aimed at automated health monitoring in young calves, hence stage two research. These AFS can measure a wide range of parameters linked to feeding and drinking patterns, including daily feed intake (4, 45, 47, 52-55, 57, 72-74), frequency and duration of rewarded and unrewarded visits (4, 45, 47, 52-55, 57, 58, 61, 62, 72, 74), drinking speed (milk) (47, 52-54), water-drinking behavior (intake, time, and frequency) (62,74), and other feeding behaviors (head-down duration at the AFS) (55, 72), time-to-bunk: time to approach feeding stations following feed-truck delivery (55, 72), and duration of unrewarded visit intervals (55). We did not find validation studies for common systems such as Förster-Technik GmbH (n = 5; Engen, Germany) or GrowSafe Systems (n = 3; GrowSafe Systems Ltd., Airdrie, AB, Canada).…”
Section: Automatic Feeding Stationsmentioning
confidence: 99%
“…For example, in parasitized beef steers (aged between 4 and 11 months) and BRD-infected dairy calves, changes in activity (e.g., lying, standing, and step counts) enabled a better disease detection than feeding behaviors such as frequency and duration of feeding and drinking (66) and feed intake (47). In identifying NCD-infected calves and BRD-infected steers, however, feeding behaviors (e.g., the number of unrewarded visits to an automated milk dispenser, DMI, and bunk visit duration) permitted a more accurate detection of disease compared with activities such as lying and standing duration (4,72). In addition, certain diseases result in behavioral changes that are easier to detect at an earlier stage.…”
Section: Changes In Other Parametersmentioning
confidence: 99%
“…2 In another experimental trial, a significant increase of Hp concentration (p < 0.001) was detected on the first day of MH challenge, which was 4 d after BoHV1 inoculation. 22 Other experimental transmission trials conducted with MH challenge also demonstrated significant increases (p < 0.01) of Hp concentration during the early stage of infection, 11,30,52 which indicates the utility of Hp as an early biomarker of BRDC, especially for bacterial infection.…”
Section: Acute-phase Protein Biomarkersmentioning
confidence: 88%
“…In identifying NCD-infected calves and BRD-infected steers, however, feeding behaviours (i.e. the number of unrewarded visits to an automated milk feeder, DMI and bunk visit duration) permitted a more accurate detection of disease compared with activities such as lying and standing duration (Sutherland et al, 2018;Kayser et al, 2020). In addition, certain diseases result in behavioural changes that are easier to detect at an earlier stage.…”
Section: Changes In Other Parametersmentioning
confidence: 99%
“…two or multiple sensors) was applied in a number of studies (n = 9, Fig. 3), in which data from accelerometers, thermometers, and AFS are integrated into one model to identify diseases including BRD (Kayser et al, 2020;Duthie et al, 2021) and NCD (Sutherland et al, 2018;Lowe et al, 2019b). Information integration, however, means more than a multiple-sensor-tool.…”
Section: Stage Three: Information Integration -Outcomes Of Modelsmentioning
confidence: 99%